'Acute leukemia in congenital methehemoglobinemia - an enigma to explore'. Issue 1 (2nd January 2019) - Al-Khafaji, Jaafar F.; Sharma, Mokshya; Nayeemuddin, Khazi; Al-Qaysi, Iman A.; Al-Mashhadani, Arshad A; Taha, Mohamed E.; Abdalla, Abubaker O.
ABSTRACT: Congenital methemoglobinemia is a rare disease, resulting in increased oxygen affinity and impaired oxygen delivery to the tissues. While there have been studies that have linked acquired methemoglobinemia in almost 79% of leukemia patients, to the best of our knowledge, this is the first case of leukemia development in a patient with congenital methemoglobinemia. Chronic deprivation of oxygen to metabolically active bone marrow can theoretically lead to hematopoietic disorders. It would be interesting to further investigate if presence of congenital methemoglobinemia is a risk factor for developing acute leukemia.